Paleomagnetism of Stony Meteorites - Nagata, Takesi (1979)
P(論文) The paleointensity for a howardite, an ulerite and three diogenites has been determined. By referring to these five values of paleointensity, the paleointensity for 6 achondrites is determined by comparing their NRM with the saturation IRM (Fuller's method). The paleointensity (F_0) for achondrites thus determined is represented by F_0=(0.11±0.02) Oe. The paleointensity for Allende C_3-chondrite is examined from various standpoints. Four other C-chondrites having reasonably stable NRM also are paleomagnetically examined. The average paleointensity for the C-chondrites is F_0=(1.02±0.09) Oe. Ordinary chondrites have a less stable NRM so that the evaluated paleointensity for ordinary chondrites is less reliable. The paleointensity for comparatively stable ordinary chondrites ranges from 0.1 to 0.4 Oe. departmental bulletin paper